(untitled) (Brazilian Journal of Oceanography, 2007)
Maurolicus stehmanni (Sternoptychidae) is a mesopelagic species of fish inhabiting the outer continental shelf and slope of the south-southeastern Brazilian (ZEE), where it presents a considerable biomass and is an important component of the trophic chain, as a forage species. On the basis of catches made with a mid-water-trawl net in 1996 and 1997, as part of the REVIZEE program, samples from 38 hauls were analyzed as regards the length structure of the population, the average length of the first maturation and the spawning seasons of the species. The analysis of histological cross-sections of the ovaries made it possible to describe the oocytic development and assess the macroscopic criteria used to classify the ovary maturation. Results showed that the average length of the first maturation occurs at 32 mm (standard length), females spawn all year round throughout the area studied and the oocytic development is asynchronous.